Adaptive Formation Control and Collision Avoidance Using a Priority Strategy for Nonholonomic Mobile Robots. (22nd February 2013) - Dai, Yanyan; Choi, Kyung Sik; Lee, Suk Gyu
This paper presents four novel collision avoidance processes for nonholonomic mobile robots to generate effective collision-free trajectories when forming and maintaining a formation. A collision priority strategy integrates the static and dynamic collision priorities to avoid a collision efficiently and effectively. In addition, it minimizes the turning angle of the follower robot and decreases system computation time. When avoiding collisions between robots, a novel collision avoidance algorithm is used to find a safe waypoint for the robot, based on the velocity of each robot. An adaptive tracking control algorithm, using the Lyapunov analysis, guarantees that the robot's trajectory and velocity tracking errors converge to zero considering parametric uncertainties of both the kinematic and dynamic models. The simulation and experiment results validate the effectiveness of the proposed method.